Ethnopharmacological and Chemical Characterization of Salvia Species Used in Valencian Traditional Herbal Preparations - Martínez-Francés, Vanessa; Hahn, Emeline; Ríos, Segundo; Rivera, Diego; Reich, Eike; Vila, Roser; Cañigueral, Salvador (Frontiers in Pharmacology, 2017)
In Valencia Region (Spain), some wild and cultivated sages are used for medicinal purposes. Among them, Salvia officinalis subsp. lavandulifolia (SL) is widely employed and known for production of Spanish sage oil and herbal products. Nevertheless, it shares the market with S. blancoana subsp. mariolensis (SB) and, to a lesser extent, with their hybrid S. x hegelmaieri (SH). The knowledge on these two species is far low and confusion between them is possible. The aim of the present paper is to improve the ethnopharmacological, morphological and chemical knowledge of these sages, and to contribute to setting up quality specifications for improving identification and distinction from other Salvia species, such as S. officinalis subsp. officinalis, S. x auriculata and S. microphylla var. microphylla. Samples were collected in Valencia Region and surrounding mountain areas during the ethnopharmacological field work. Twenty-nine medicinal uses were reported for SL, 13 of them being also recorded for SB. Of particular interest is a homemade liquor, used as digestive and known as "salvieta", which is mainly prepared with SB. The macro- and microscopic characters are insufficient for identification of cut, crushed or powdered material. The study of the essential oil content and a HPTLC (High Performance Thin Layer Chromatography) fingerprint of their extracts could help to distinguish SB from the other sages. The essential oil from dried aerial parts of SB (content: 1.8-4.5%) was characterized by GC-FID (Gas Chromatography with Flame Ionization Detector) and GC-MS (Gas Chromatography coupled to Mass Spectrometry) showing a composition close to that currently accepted for Spanish sage essential oil in the European Pharmacopoeia, ISO (International Standard Organisation) and UNE (Una Norma Española) standards, with 1,8-cineole (13.7-45.7%) and camphor (12.1-28.6%) as major constituents. HPTLC methods, based on the analysis of hydroalcoholic and dichloromethane extracts, allowed to distinguish SB from other Salvia taxa currently found in Valencia region, except from its hybrid SH. This interdisciplinary study, that combines popular knowledge with botany and chemistry, allows to identify the raw herbal material from SB and to distinguish it from other Salvia species, ensuring a proper commercialization as herbal teas or for the preparation of spirits.